Exploring the potential of halal gelatin from chicken by-products: a review - Pertiwi, Chafiyani Wulan; Nuzulina, Baiq; Umah, Da'iyatul (Universitas Airlangga, 2025)
Gelatin is a product of partial hydrolysis of collagen from bones, skin, and animal tissues. Gelatin is frequently used in the food industry. However, Indonesia itself is not a gelatin-producing country. Indonesia's gelatin needs are dependent on imports from other countries. This activity is highly sensitive because the raw materials for gelatin typically consist of pig and its byproducts, whereas Indonesia is a predominantly Muslim-populated country. This article review discusses the potential of chicken byproducts as a halal alternative of gelatin from related journals published over the past decade. Gelatin produced from chicken byproducts has varying characteristics, including gel strength, gelling point, melting point, and viscosity. Chicken byproducts’ gelatin can fill all categories of gelatin, ranging from low to high gel strength. This makes it applicable to various industries, particularly in the food and pharmaceutical sectors. However, to ensure its halal status, it is necessary to verify that the byproducts used as the raw material for gelatin originates from halal chicken slaughter. Keywords: Alternative, By-Product, Halal, Pre-Treatment, Poultry